Generalized boundary values of solutions of quasilinear elliptic equations with linear principal part - Lopushanskaya, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish conditions for the nonlinear part of a quasilinear elliptic equation of order 2m with linear principal part under which a solution regular inside a domain and belonging to a certain weighted L_1-space takes boundary values in the space of generalized functions.